A New Approach of Per-Cutaneous Abdominal Manipulation for the Correction of Uterine Torsion in Goats - Cholakkal, Ibraheem Kutty (International Journal of Livestock Research, 2021)
Uterine torsion is one of the major causes of dystocia in small ruminants. Instead of the usual method of rolling the animal, a novel method of abdominal manipulation was attempted for correction of uterine torsion in goats. After assessing the position and direction of torsion, hindquarters of the animals were lifted by an attendant. Palpation of the gravid uterus through the ventral abdomen was attempted keeping both hands outside or one hand inserted per vaginum and de-torsion was tried. Favourable response was indicated by the emerging order of uterine contents and accessibility of foetus per vaginum. Dystocia could be corrected in all the four goats attended thereby. Lifting the hindquarters moves abdominal organs forward so that gravid uterus hangs freely making per-cutaneous de-torsion easier. It is concluded that per-cutaneous manipulation together with lifting the hindquarters forms an easier approach for the correction of uterine torsion in goats.